Da'wah in the Modern Era: Adapting Tradition with Innovation - Sri Mawarni; Muthoifin (Walidem Institute and Publishing, 2024)
Da'wah in the modern era requires adaptation to tradition with relevant and effective innovations. The purpose of this study is to identify the da'wah methods used in adapting traditions with innovations and the results achieved from this approach. This research uses a qualitative approach with data collection techniques through interviews and observations of da'wah practitioners and related literature studies. The da'wah methods used include the use of information technology, social media, and a more contextual approach under the demands of the times. In addition, da'wah also adapts local traditions, such as culture and customs, by paying attention to universal values in Islam. The result of this approach is an increase in the accessibility of da'wah to the wider community, the strengthening of cultural Islamic identity, and an increase in a more comprehensive understanding of religion. By combining tradition with innovation, da'wah in the modern era can achieve better goals in spreading religious messages and strengthening the connection between religion and people's daily lives. This research provides valuable insights for the development of da'wah strategies that follow the demands of the times and the needs of the community.